Pengaruh Pemberian Pupuk Nutrisi Saputra dan Intervalnya Pemberiannya terhadap Pertumbuhan dan Hasil Tanaman Cabai Rawit (Capsicum frutencens L) - Zainudin Zainudin (Agrifarm : Jurnal Ilmu Pertanian, 2012)
Effect of fertilizing manure nutrients saputra and intervals of administration on the growth and yield of cayenne pepper (Capsicum frutescens.L). The research objective was to determine the dose of fertilizer nutrients Saputra and intervals of administration on the growth and yield of cayenne pepper (Capsicum frutescen L). Research carried out for ± 4 months, from September to December 2010, starting from land preparation to harvest, in the district. Samarinda Ilir, Samarinda, East Kalimantan. Research using randomized block design (RBD), with a 4 x 3 factorial analysis composed with 3 replications, the main factor is the dose Fertilizer Nutrients Saputra, which consists of 4 levels, ie without fertilizers (p0), 6 ml plant-1 is equivalent to 120 plot ml -1 (p1), 12ml plant-1 plant is equivalent to 240 ml -1 (p2) -1 plant 18ml equivalent to 360ml of plant-1 (p3), 24 ml of plants equivalent to 480ml plant -1 -1 ,, factor The second is the interval Giving Fertilizer Nutrients saputra which consists of three levels ie 7 DAP (a1), 14 DAP (a2), 21 DAP (a3). The results showed that fertilizer nutrients Saputra very real impact on the average age of flowering 80%, the average number of productive branches, the average number of fruit crops, the average fresh weight and the average yield per hectare, as well as significantly affected the average length of the best fruits in the treatment of p3: 2.96 cm. Effect of fertilizer NS intervals showed significant effect on plant height at 15 days after planting and the number of productive branches. As well as highly significant to the average fresh weight and yield per hectare is the highest a3 treatment: 4.04 tonnes / ha. NS interaction effects of fertilizer application significantly affected the plant height at 15 DAP and highly significant to the weight of the fruit and the result per hectare. Average yield per hectare is the highest p3a3 treatment: 8.19 tonnes / ha.